KONSEP ADAB BELAJAR (STUDI KOMPARASI KITAB TANBIHUL MUTA’ALIM DENGAN KITAB TAYSIR AL- KHOLLAQ) - Mat Rohim (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2019)
Moral education or etiquette is an inseparable part in the education process. Lack of attention from the world of education about the behavior or attitudes of students to their teachers or vice versa, such as the example of a lack of courtesy or tawadu 'a student to his teacher, The results of the study stated that the concept of learning manners in the book Tanbi> hul Muta'allim and the Book of Taysir al-Kholla>q namely: the manner to learn towards Allah SWT. The manner to learn towards yourself. Civilized learning of fellow human beings. The manner to learn the knowledge learned. Basically the biggest difference between the study of civilized learning KH. Ahmad Maysu> r Sindy at-Thursidi> with Ha> fiz} Hasan Al-Mas'u>di is at the technical level, while the principles and aspects are the same. One thing that needs to be underlined is that the differences between the two are not contradictory differences, but differ only in the scope of ideas. Ha> fiz} Hasan Al-Mas'u>di discussing about the etiquette of learning with his fellow students, while KH. Ahmad Maysu>r Sindy at-Thursidi> no.